Analysis Thermal Pada Solid dan Ventilated Disk Brake Pada Mobil Hemat Energy Pagaruyuang Team UNP - Wanda Afnison; Wagino Wagino; Nuzul Hidayat; Muslim Muslim; Masykur Masykur (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2021)
This study discusses the thermal analysis of the disc brakes used in UNP energy-efficient cars. There are three types of disc brake designs that are simulated, namely solid disc brake, circular hole ventilated and vane ventilated types. Using the finite element method, the three disc brake designs analyzed the characteristics of the heat received from the braking process. Disc brakes with better heat dissipation ability are the most suitable type to use. From the simulation results, the ventilated (circular hole) disc brakes have the best heat dissipation capability with a maximum temperature of 635,520 K, lower than the vane and solid types where the maximum is obtained. temperatures of 5700 K and 809.50 K . The vane type disc brake design is a disc brake design with the worst heat dissipation capability which has the highest final temperature of 809.50 K.Keywords—Thermal analysis, disk brake, heat, high efficiency vehicle